Repercussions of juvenile diagnosis of leukemia in patients and their families: integrative review (Research, Society and Development, 2022)
Objectives: This study aims to analyze repercussions that a leukemia diagnosis may have on the diagnosed children and its family, as well as identify nursing interventions capable of minimizing its impacts on both. Methodology: Integrative review of the literature, using the international databases Cochrane Library, Medline and Scopus. Data collection was conducted from December 2021 to February 2022 by using combinations of the following descriptors: Leukemia, Child, Family, Nursing, “Sickness Impact Profile”, “Quality of Life”. Results: After inclusion and exclusion criteria were applied, 10 papers were selected and used in the elaboration of two categories: “Repercussions of a Leukemia diagnosis on children and their families” and “Nursing interventions to attenuate impacts on patients and their families”. Cancer diagnoses were observed to affect patients physically and mentally, producing symptoms such as: pain, fatigue, paleness, low self-esteem, anxiety and depression. Furthermore, the lack of bonds or proper communication between medical team, patients and family was singled out as the main obstacle to proper nursing care. Conclusion: Nursing interventions must be adopted in accordance with the symptoms shown by children and teenagers, with the aim of enabling singular care practices capable of promoting the development of bonds between all parties involved in the treatment, producing a safety sensation in parents and patients and maximizing effectiveness of assistance whilst minimizing pain for both.